DINAMIKA PROSES PEMEKARAN KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2008-2012 - ZULKARNAIN, ARIANDI A; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Regional growth is a form of regional autonomy that should be supported by all elements of the local and central levels of society , which is based on Law No. 32 of 2004 and Law 19 of 2008 which has been set up how terotori policy laid out in the merger , abolition , and expansion . Subdistrict Sentajo Kingdom in full formation of political nuances and dynamics of a number of public rejection of the District Benai . Departing from the above phenomenon researchers are interested in studying the formation of the District Sentajo Kingdom with the title " the District Redistricting Process Dynamics Sentajo Kingdom Regency Kuantan Singingi year 2008-2012 "Which became the real fundamental problem in the District Sentajo Kingdom expansion process are political elite interests therein , as seen from Government Regulation No.19 of 2008 in terms of Article 4 of the Special Committee ignores the point C and D , which occurs rejection of the District Society Benai due to absence communication to the public component of the District Benai related to the formation and retrieval of the sub Benai village . Rejection happens starting from the formation of the District crews discourse until the formation of the District Sentajo Kingdom became a phenomenon in the formation of the District that is not widely accepted for the components involved in the expansion of both local and regional preparations parent . This rejection has been submitted to the Government the District of Benai area and Riau Province . But political interest in the elite division so strong that the District continue to implement new formation before completing the existing rejection problem . Lack of socialization of the local government in the formation of the District Sentajo Kingdom is also a major effect on the process that led to the public on the pros and cons Kecematan Benai .It can be concluded , this research the existence of the interests of the political elite and especially local governments Singingi Kuantan Local legislators to voice support in the next election by ignoring some processes in Law 19 of 2008 which regulates Kecataman Formation . The local government has not been wise in the policy-making process as it should have to promote the constitutional principle of public policy , democratic , rational and non-discrimination. Keyword : Regional Autonomy , Redistricting Regional , District